A numerical study on the effect of magnetic heating to crude oil-nanofluid flow for enhanced oil recovery - Tan, P.H. (Penerbit UTM Press, 2020)
Magnetic heating of crude oil mixed with nanoparticle for heat transfer mechanism enhancement has received much attention in enhanced oil recovery (EOR). In the present work, the heat transfer of Fe3O4, Al2O3, CuO, Cu nanoparticles mixed in crude oil is theoretically investigated. The mathematical model of magnetic field heating in reservoir is represented by the channel flow of crude oil-nanofluid subjected to a longitudinal spatially varying magnetic field. The viscous incompressible flow is bounded by nonisothermal walls. The coupled nonlinear partial differential equations (PDEs) are solved numerically using an unconditionally stable time integration and finite element method. The numerical results are validated against data available in literature. The physical aspects of the crude oil-nanofluid flow and heat transfer are discussed in terms of several pertinent parameters such as solid nano fraction, skin friction, magnetic, Hartmann and Nusselt numbers. It is found that the enhancement of heat transfer increases with the magnetic number and solid nano fraction while decreases with the increase in Hartmann number. It is shown that, the addition of nanoparticle and increment of magnetic number is effective in the localised heating. In addition, the heat transfer of Fe3O4, Al2O3, CuO, Cu nanoparticles in crude oil mixed are investigated and assessed against each other. It is observed that, the heating mechanism would not be as effective for high electrically conducting nanoparticles. The results also indicate that nanoparticle with high thermal conductivity and low electrical conductivity is preferable in obtaining susceptible thermal heating for the EOR. Â© 2020 Penerbit UTM Press. All rights reserved.